The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Geo-China 2016 2016
DOI: 10.1061/9780784480083.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sample Preparation Methods on the Properties of a Cohesive Soil

Abstract: This paper investigates the effects of sample preparation method on the density and California bearing ratio (CBR) of a cohesive soil. The samples were prepared at two moisture contents (dry and wet of optimum) by consolidation and compaction methods with various efforts (energy). The density and CBR of these samples were than measured and compared. Results of these tests indicate that, at dry of optimum, samples prepared by compaction method yielded higher density and CBR than samples prepared using consolida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…According to the Unified Soil Classification (UCS) system, these two materials can be classified as well-graded gravel with sand (GW) and silty clay with sand (CL-ML), respectively. Previous study (Yang et al, 2016) has shown that a weak subgrade layer (CBR = 2%) can be obtained by consolidating the clay at a water contain of 18% with a normal stress of 84 kN/m 2 . Therefore, the subgrade layer was prepared by consolidating 1210gm/layer of wet clay in three layers in a 6"-diameter compaction mold using a loading frame as shown in Fig.…”
Section: Testing Programsmentioning
confidence: 99%
“…According to the Unified Soil Classification (UCS) system, these two materials can be classified as well-graded gravel with sand (GW) and silty clay with sand (CL-ML), respectively. Previous study (Yang et al, 2016) has shown that a weak subgrade layer (CBR = 2%) can be obtained by consolidating the clay at a water contain of 18% with a normal stress of 84 kN/m 2 . Therefore, the subgrade layer was prepared by consolidating 1210gm/layer of wet clay in three layers in a 6"-diameter compaction mold using a loading frame as shown in Fig.…”
Section: Testing Programsmentioning
confidence: 99%